APPLICATION OF PROBLEM-BASED LEARNING MODEL THROUGH ONLINE LEARNING ON LEARNING MOTIVATION OF STUDENTS OF SMAN 3 ENREKANG (International Conference on Social and Islamic Studies, 2022)
Learning that is done online (on a network) requires teachers to be more creative in teaching so that students are more motivated in learning, for example by using learning models that support students to actively participate even though it is done online. This article aims to determine the learning motivation of students during online learning using a problem-based learning model. This type of research is an experimental study with a Pre-test Post-test Control Group Design. The population in this study were all students of class XI MIPA, total 205 people. The sample of this research was class XI MIPA 1 which amounted to 32 people and class XI MIPA 2 which amounted to 32 people. The sampling technique used is probability sampling (random sampling). The instrument used was a learning motivation questionnaire. The data analysis technique used is the analysis of the Independent Samples t Test. The results showed the value of sig. (2-tailed) of 0.000 (p < 0.05). From the research data, it can be concluded that there are differences in the learning motivation of students who are taught using a problem-based learning model through online learning and those taught without using problem-based learning in class XI MIPA students of SMAN 3 Enrekang. The results of this study imply that in increasing students' learning motivation, teachers can use problem-based learning.